Process of population ageing in Peru as a new social and demographic reality - Ticona Fernández Dávila, Rubén (2021)
This article is about the process of population ageing in Peru and Latin America, in the context of the pandemic. During the last 20 years, Latin American people have been ageing. This scenario presents several dilemmas for governments. Peru has faced this situation for about 10 years. The latest statistical figures have shown this demographic trend. This situation stablishes some challenges for the Peruvian government. Therefore, the situation of the elderly, the existing social policies and the social service programs will be analyzed. Methodologically, the research presents a theoretical discussion, a bibliographic review, and a systematization of various experiences.